Scalp Necrosis Revealing Severe Giant-Cell Arteritis - Safa Idoudi; Marouene Ben Kahla; Fares Mselmi; Badreddine Sriha; A. Guiga; Samia Ayachi; Colandane Belajouza; Mohamed Denguezli (Case Reports in Medicine)
Giant-cell arteritis (GCA), also referred to as temporal arteritis, is the most common primary vasculitis of the elderly involving the extracranial branches of the carotid arteries, in particular, the temporal artery. Patients usually present with temporal headaches, visual impairment, fever, and scalp tenderness. Scalp necrosis associated with GCA is a rare occurrence with approximately 100 cases reported in the literature to date. It is a therapeutic emergency requiring urgent management as it may lead to irreversible loss of vision. To increase awareness of this severe complication, we report a patient with a scalp necrosis revealing a GCA.